The Contribution of Al Islam Kemuhammadiyahan to Character Education: A Case Study Among Non-Muslim Students - Khatimah, Khusnul; Hamid, Ade Ismail Ramadhan; Asyifah, Intan; Asriyadi, Fitroh (INTERACTION: Jurnal Pendidikan Bahasa, 2024)
This study explorethe contribution of the Al Islam Kemuhammadiyahan (AIK) course to the character education of non-Muslim students at the Muhammadiyah University of East Kalimantan. The aim is to identify how AIK influences the formation of values ​​such as tolerance, justice, devotion, and social responsibility in non-Muslim students. With a case study approach, this study involved non-Muslim students who had taken AIK as subjects. Data were collected through in-depth interviews and participant observations to understand their experiences and perceptions of the values ​​taught in AIK. The results of the analysis showed five main themes: tolerance, devotion, justice, attitude change, and openness in interfaith dialogue. AIK was shown to encourage non-Muslim students to respect religious and cultural differences, form an attitude of mutual respect, and increase a sense of social responsibility. This study provides new insights into the importance of AIK in creating an inclusive, tolerant, and multicultural educational environment. It is hoped that these findings can support the development of character education in other multicultural universities and strengthen harmony between students from various religious backgrounds.